2009
DOI: 10.1111/j.1365-2966.2009.14878.x
|View full text |Cite
|
Sign up to set email alerts
|

On the quasi-periodic oscillations in magnetars

Abstract: We study torsional Alfvén oscillations of magnetars, that is neutron stars with a strong magnetic field. We consider the poloidal and toroidal components of the magnetic field and a wide range of equilibrium stellar models. We use a new coordinate system (X, Y), where and and a1 is the radial component of the magnetic field. In this coordinate system, the one+two‐dimensional evolution equation describing the quasi‐periodic oscillations (QPOs), see Sotani et al., is reduced to a one+one‐dimensional equation w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
111
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(126 citation statements)
references
References 23 publications
10
111
2
Order By: Relevance
“…Those QPO frequencies are also detected by us. In addition, we have detected several more QPO frequencies (21, 59, and 116 Hz) with the Bayesian method, which were also predicted by Colaiuda et al (2009). signal has a higher significance in a subinterval of the considered time interval and the fast convergence of the MCMC procedure already provided.…”
Section: Observational Data and Results Of Analysismentioning
confidence: 93%
See 3 more Smart Citations
“…Those QPO frequencies are also detected by us. In addition, we have detected several more QPO frequencies (21, 59, and 116 Hz) with the Bayesian method, which were also predicted by Colaiuda et al (2009). signal has a higher significance in a subinterval of the considered time interval and the fast convergence of the MCMC procedure already provided.…”
Section: Observational Data and Results Of Analysismentioning
confidence: 93%
“…In particular, by studying Alfvén oscillations, in the stellar interior and in the absence of crust, Colaiuda et al (2009) could reveal the existence of Alfvén continua (as suggested by Levin 2007). The edges of this continuum have been used to explain the observed QPOs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the central objects in SGRs are considered to be magnetars which are strongly magnetized neutron stars, the discovered QPOs in giant flares could be due to neutron star oscillations. In order to explain these QPO frequencies theoretically, a lot of numerical attempts have been done not only by the shear oscillations in the crust of neutron stars but also by the magnetic oscillations [17,18,19,20,21,22,23,24,25,26,27]. In addition, ascribing the observed QPOs to shear oscillations in the crust of neutron stars, the possibilities are also pointed out to reveal the properties of inhomogeneous nuclear matter in the crust [28,29,30,31,32].…”
Section: Introductionmentioning
confidence: 99%